Accumulation, excess, childhood : toward a countertopography of risk and waste - Katz, Cindi (Documents d’Anàlisi Geogràfica, 2011)
This piece grows out of my on-going project, ‘Childhood as Spectacle’, and my enduring concern with social reproduction and what it does for and to Marxist and other critical political-economic analyses. After more than 30 years of Marxist-feminist interventions around these issues, symptomatic silences around social reproduction remain all too common in analyses of capitalism. Working through these issues and their occlusion, I offer what I hope is a useful and vibrant theoretical framework for examining geographies of children, youth, and families. Building this framework calls into play three overlapping issues; neoliberal capitalism in crisis and David Harvey’s notion of accumulation by dispossession, my ideas around childhood as spectacle, as a cultural formation associated with contemporary political economic crisis and its figuration of the child as waste, and how this figuration might be turned around to find libratory potential in and from the site of children’s play and time.